the relationship between career adaptability and future time perspective with work readiness among fresh graduates of higher education institutions in bangkalan regency - Ulfatul Munawaroh; Niken Titi Pratitis; Mamang Efendy (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
This study aims to examine the relationship between career adaptability and future time perspective with the work readiness of fresh graduates. This study uses a quantitative approach with a correlational design and involves 193 fresh graduate respondents. The instruments used include scales of career adaptability, future time perspective, and work readiness that have been tested for validity and reliability. Data analysis was performed using nonparametric tests with Spearman's Rho method. The results showed that career adaptability and future time perspective were significantly positively related to work readiness. These findings indicate that students with high career adaptability and future time perspective tend to be more prepared to enter the workforce, both in terms of technical skills and mental readiness. This study emphasizes the importance of developing these two variables in preparing students for the dynamic world of work.